2018
DOI: 10.1007/s00167-018-5162-5
|View full text |Cite
|
Sign up to set email alerts
|

The dimensions of the hip capsule can be measured using magnetic resonance imaging and may have a role in arthroscopic planning

Abstract: Purpose The purpose of this study was to systematically evaluate the dimensions and thickness of the hip joint capsule. Secondarily, the study assessed whether there were any described correlations between capsule thickness and stability of the hip joint. Methods Four databases (PubMed, Ovid [MEDLINE], Cochrane Database, and EMBASE) were searched from database inception to May 2018, and two reviewers independently and in duplicate screened the resulting literature. Methodological quality of all included papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…The methodology of the following systematic review was adopted from a previous study. 29 This systematic review was performed in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Three online databases (Embase, PubMed, and Ovid [MEDLINE]) were searched from database inception until May 19, 2018, for studies investigating the predictors of clinical outcomes after hip arthroscopic surgery for FAI.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of the following systematic review was adopted from a previous study. 29 This systematic review was performed in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Three online databases (Embase, PubMed, and Ovid [MEDLINE]) were searched from database inception until May 19, 2018, for studies investigating the predictors of clinical outcomes after hip arthroscopic surgery for FAI.…”
Section: Methodsmentioning
confidence: 99%
“…Images of the joint capsule, including the zona orbicularis, have been analyzed previously. However, these studies have mainly focused on the ability to visualize (Malagelada et al, 2015;Wagner et al, 2012) or the capsular thickness (Kay et al, 2020;Strickland et al, 2018); the articular cavity surrounded by the joint capsule has never been studied quantitatively. Micro-CT analysis in the present study revealed that the inward protrusion of the joint capsule surrounded the narrowest area of the articular cavity, which was ovoid T A B L E 1 Area of the articular cavity and its ratio to the neck of femur Note: The narrowest cross-sectional area of the neck of the femur perpendicular to its longitudinal axis, and those of the articular cavities perpendicular to the same axis, were measured.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the capsule can be measured using MRI and may be helpful in guiding capsular management. Patients with thicker capsules are known to have less laxity in their hip compared to patients with thinner capsules [94]. Table 26.4 summarizes the common indications and contraindications for capsular closure.…”
Section: Capsule Closurementioning
confidence: 99%